Comparative transcriptome analysis of Brucella melitensis in an acidic environment: Identification of the two-component response regulator involved in the acid resistance and virulence of Brucella. (February 2016) - Liu, Qianhong; Liu, Xingyu; Yan, Feng; He, Yuhua; Wei, Jie; Zhang, Yuanyuan; Liu, Lu; Sun, Youpeng
Abstract: Brucella melitensis, encounters a very stressful environment in phagosomes, especially low pH levels. So identifying the genes that contribute to the replication and survival within an acidic environment is critical in understanding the pathogenesis of the Brucella bacteria. In our research, comparative transcriptome with RNA-seq were used to analyze the changes of genes in normal-medium culture and in pH4.4-medium culture. The results reveal that 113 genes expressed with significant differences (|log2Ratio| ≥ 3); about 44% genes expressed as up-regulated. With GO term analysis, structural constituent of the ribosome, rRNA binding, structural molecule activity, and cation-transporting ATPase activity were significantly enriched (p-value ≤ 0.05). These genes distributed in 51 pathways, in which ribosome and photosynthesis pathways were significantly enriched. Six pathways (oxidative phosphorylation, iron-transporting, bacterial secretion system, transcriptional regulation, two-component system, and ABC transporters pathways) tightly related to the intracellular survival and virulence of Brucella were analyzed. A two-component response regulator gene in the transcriptional regulation pathway, identified through gene deletion and complementary technologies, played an important role in the resistance to the acid-resistance and virulence of Brucella . Graphical abstract: Highlights: A description of 113 genes in an acidic environment of Brucella through comparative transcriptome analysis. These genes distributed in 51 pathways, in which ribosome and photosynthesis pathways were significantly enriched. Six pathways tightly related to the intracellular survival and virulence of Brucella were analyzed. Confirmation of the two-component response regulator involved in the acid resistance and strength of Brucella. Abstract : A description of 113 genes in an acidic environment through comparative transcriptome analysis; and a confirmation of the two-component response regulator involved in the acid resistance and strength of Brucella .